Reportable facts and a personal touch: the functions of direct quotes in online news - Landert, Daniela (The pragmatics of quoting now and then, 2015)
Das Kapitel 1. Reportable Facts and a Personal Touch: The Functions of Direct Quotes in Online News erschien in The Pragmatics of Quoting Now and Then auf Seite 29.
Gesehen am 04.04.2024